Do sources of knowledge transfer matter? A firm-level analysis in the PRD, China - Wan-Hsin Liu (Kiel Institute for the World Economy (IfW), 2009)
This paper investigates whether knowledge transferred from different sources matter differently for carrying out different innovation outcomes, using a firm-level dataset collected in the Pearl River Delta (PRD) in China. It also investigates whether companies in the PRD in China tend to innovate in a similar way as companies in the Asian Newly Industrialised Economies (NIEs) did decades ago. Our estimation results suggest that companies in the PRD, as companies in the Asian NIEs, strongly rely on sourcing from their OEM customers but not on own R&D activities to implement innovative processes to increase production efficiency. In contrast, they engage in own R&D activities in order to develop innovative products, to realise higher innovation sales and to create new knowledge qualified for patenting. In addition to own R&D activities, they rely on sourcing knowledge from different sets of sources to support them to carry out the last three types of innovation outcomes.
Keywords: O1; O3; R1; 330; Innovation; knowledge transfer; knowledge production function; flying geese model; China; Wissenstransfer; Industrielle Forschung; Lieferanten-Kunden-Beziehung; Innovation; Entwicklungskonvergenz; China; Ostasien